Study on Mechanical Properties of Banana Fiber-Reinforced Materials Poly (Lactic Acid) Composites - Tuan Anh Nguyen; Thi Huong Nguyen (International Journal of Chemical Engineering)
Synthetic materials reinforced with natural fibers are attracting great attention of scientists and researchers. Sustainability and eco-friendly nature along with easy availability and low cost are the key reasons. In this work, a natural fiber such as a banana fiber was investigated to create bioavailable materials while enhancing mechanical properties. The banana fiber was extracted from banana sheath by the mechanical method combined with chemical treatment with NaOH 1, 2, 3, 4, and 5%. Treatment of the banana fiber with NaOH effectively removes other impurities from the fiber surface and the fiber surface becomes rough, increasing the compatibility and bonding between banana fiber and PLA. The reported optimum NaOH concentration was 5% banana fiber used for the material polylactic acid (PLA) composite/banana fiber. The composites (BF) were prepared by the hot melt mixing method. The results showed that 20% by weight of banana fiber gave good results and the mechanical strength values kept at the specified level (tensile strength: 52.57 MPa, flexural strength: 70.35 MPa, impact strength: 155.45 J/m and hardness: 23.8 Hv). SEM observations showed visual evidence that surface impurities were removed from the fiber by NaOH treatment.